Philosophical and general scientific principles of teaching training development of future engineers of food technology for creative activities - Lazarieva, T.; Koralevski, J.; Tarasuk, A. (Problems of Engineer-Pedagogical Education, 2018)
The philosophical and general scientific principles of design methodology of training future engineers - technologists of food industry to creative profession were provided in the article. Found that categories of philosophy have significant methodological value and can be used for creative activity of future engineers the food industry. The basic philosophy categories were considered: material and ideal, space and time, cause and effect, necessity and chance, possibility and reality, and common identity, content and form, essence and phenomenon, conflict and development. It was established that the content of methodical system of training future engineers of the food industry to the creative professional activities must be submitted integrated spatial and logical three-dimensional models, where the first dimension is the system knowledge of objects food industry, the second dimension is the system of criteria and parameters, and the third measurement of a system of techniques and methods for solving creative tasks for the development and improvement of facilities of the food industry. This model reflects the spacetime unity declarative and procedural components of creative professional activity of future engineers of the food industry.